Assessment of nitrogen diagnosis methods in sunflower - Tovar Hernandez, Sergio (2021)
Nitrogen deficiency can severely limit sunflower (Helianthus annuus L.) grain yield and quality. Our objective was to evaluate N diagnosis methods based on: (a) pre-plant soil nitrate-nitrogen (NO3––N) test (PPSNT) and soil N mineralized in short-term anaerobic incubation (Nan), (b) Greenness index (GI) and the normalized difference vegetation index (NDVI) measured at 6 (V6) and 12 (V12) leaves, and (c) grain nitrogen concentration (Nc). Seventeen experiments were carried out between 2010 and 2019 in Argentina, evaluating nine N rates (0, 30, 40, 60, 80, 90, 120, 150, and 160 kg N ha–1). The GI, NDVI, N sufficiency index and relative normalized difference vegetation index (NDVIr) were determined at V6 and V12 growth stages. On average, yield response to N was 492 kg ha–1 and Nc response was 0.25% in 9 and 11 responsive experiments, respectively. The inclusion of Nan improved the PPSNT diagnosis method. The critical N availability (PPSNT + fertilizer N) threshold was 115 kg N ha–1 for experiments with low Nan (<60 mg kg–1), and 90 kg N ha–1 for experiments with high Nan (>60 mg kg–1). The NDVIr at V12 allowed monitoring the crop N status with a 0.95 critical threshold. The Nc adequately diagnosed N deficiencies and the critical threshold was 2.26%. Also, Nc was predicted from the ratio between N availability and grain yield (R2=.39). Our results would allow to better estimate N availability to recommend adequate N fertilizer rates for sunflower aiming to optimize grain yield and quality, and minimize the economic and environmental cost of fertilization.